2017
DOI: 10.1093/ntr/ntx102
|View full text |Cite
|
Sign up to set email alerts
|

Early Subjective Sensory Experiences with “Cigalike” E-cigarettes Among African American Menthol Smokers: A Qualitative Study

Abstract: The subjective sensory experiences associated with initial e-cigarette product use are associated with use patterns. Subjective sensory experiences may also help understand the differences in the appeal, satisfaction, and harm-reduction potential of the rapidly evolving diverse types of products emerging in the marketplace. How products meet the sensory needs of smokers wanting to switch or quit smoking may influence adherence and success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Our results generally contrast with a previous study of AA adults switching from smoking to first generation ECs which found that the majority (73%) reported an unsatisfactory experience [ 14 ]. One of the most important distinguishing characteristics between first generation cigalikes and fourth generation NSPS ECs is the nicotine salt formulation which provides more efficient nicotine delivery [ 20 , 26 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results generally contrast with a previous study of AA adults switching from smoking to first generation ECs which found that the majority (73%) reported an unsatisfactory experience [ 14 ]. One of the most important distinguishing characteristics between first generation cigalikes and fourth generation NSPS ECs is the nicotine salt formulation which provides more efficient nicotine delivery [ 20 , 26 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Racial and ethnic disparities in exclusive switching to ECs could exacerbate the burden of tobacco-related death and disease among disadvantaged populations [ 13 ]. A previous prospective qualitative study of AA people who smoked menthol cigarettes switching to first generation cigalikes found that the majority (73%) reported an unsatisfactory experience [ 14 ]. More information on the experience of ECs among AA and Lx individuals who smoke is needed to evaluate the viability of ECs as a harm reduction strategy.…”
Section: Introductionmentioning
confidence: 99%
“…53 Appeal is complex and encompasses attractiveness of the product, sensory characteristics, and subjective satisfaction as well as cost, accessibility, and marketing practices. 40,5456 A product with minimal appeal will not be adopted or used extensively (e.g., over-the-counter NRT 57,58 ). NNPs must be sufficiently appealing to encourage a larger portion of smokers to switch from the high- to the low-harm products.…”
Section: A New Frameworkmentioning
confidence: 99%
“…NNPs must be sufficiently appealing to encourage a larger portion of smokers to switch from the high- to the low-harm products. 54 Dependence (y-axis) refers to the potential for the product to provide satisfaction and induce a degree of addiction, which is a function both of its pharmacological and its subjective rewarding and sensory properties. Dependence can reflect a response to withdrawal and to enjoying, liking or needing nicotine’s well-documented desirable effects, like improved alertness, concentration, mood and memory.…”
Section: A New Frameworkmentioning
confidence: 99%
“…For example, some participants explicitly stated a preference for cigarettes and were willing to go outside to use them, but not e-cigarettes. This suggests that if smokers perceive that e-cigarettes cannot outcompete traditional cigarettes on nicotine delivery, taste, and ‘whole body’ satisfaction, then they may not switch to e-cigarettes 23 , and they may not comply with indoor smoke-free policies that prohibit e-cigarette use.…”
Section: Discussionmentioning
confidence: 99%